Sosialisasi dan Pendampingan Persiapan Peralihan Aplikasi Sistem Informasi Pelaporan Keuangan Menuju Networking-Web Based Application Pada Koperasi Karyawan PT. Pusri - Arista Hakiki; Yusnaini Yusnaini; Burhanudin Burhanudin (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2023)
The purpose of this activity is to carry out socialization and assistance in preparation for the transition of financial reporting information system applications to Networking-Web Based Applications at the Koperasi Karyawan PT. PUSRI. The benefit of this activity is that it can contribute to the development of cooperative business in Palembang, especially in the use of financial reporting system applications. The mentoring method is by providing explanations about the financial reporting system applications used by cooperative actors, simulations, use trials, discussions and feedback. The main output of this activity is the creation of a financial reporting system application that can be used routinely and optimally by cooperative actors in Palembang, especially at Kopkar PT. Pusri Palembang. The target and target audience for this activity are all accounting and finance staff as well as cooperative management. With this service activity, cooperative actors can understand the importance of the role of preparing simple financial reports for cooperatives which are useful in showing the results of their business (profit/loss) to analyze the development of their business and by using networking-web based applications it makes it easier for MSMEs to prepare financial reports. more easily and quickly